Enhancing the student experience with the use of a dedicated subject website - Hilliam, Rachel; Arrowsmith, Gaynor (MSOR Connections, 2019)
It is crucial not only to support students at all stages of their student journey, but also to create a space where they can benefit from peer support and interact with the wider mathematics and statistics (M&S) community. In a society awash with social media, it is possible to create online spaces that complement and enhance existing communities available in traditional face-to-face courses, or to provide such an environment for students who learn at a distance. The School of Mathematics and Statistics at The Open University (OU) has recently consolidated existing resources into a website resulting in an active and vibrant community of learners. The site contains resources, which students access at appropriate points in their student journey through M&S modules and qualifications. These resources are complemented by a number of dedicated and well-used online forums. In particular, a forum providing course choice information. Discussions in the forum have ultimately led to improvements in the structure of M&S qualifications, influencing the content of new modules, more effective assessment strategies, and better ways of supporting students. It is a true community of learners, where everyone - students, academics and educational advisors - all contribute, learn from each other, and shape the student experience.